Development, Proliferation, and Growth of the Mammalian Heart - Günthel, Marie (Mol Ther, 2018)
During development, the embryonic heart grows by addition of cells from a highly proliferative progenitor pool and by subsequent precisely controlled waves of cardiomyocyte proliferation. In this period, the heart can compensate for cardiomyocyte loss by an increased proliferation rate of the remaining cardiomyocytes. This proliferative capacity is lost soon after birth, with heart growth continuing by an increase in cardiomyocyte volume. The failure of the injured adult heart to regenerate often leads to the development of heart failure, a major cause of death. With the recent observation of a small fraction of cardiomyocytes that appear to have retained the proliferative capacity within the adult heart, as well as the identification of developmental pathways such as the Hippo-signaling pathway that can invoke mature cardiomyocyte proliferation, more studies are taking a knowledge-based mechanistic approach to heart regeneration. A key question being asked is if this knowledge can be used therapeutically to reinitiate cardiomyocyte proliferation after injury such as myocardial infarction. In this respect, uncovering and understanding the mechanisms and conditions that give rise to a fully functional and adaptive heart in the developing embryo could provide us with the answers to many of the questions that are now being asked.